Location of the Genes for 16S and 23S Ribosomal RNA in the Genetic Map of Escherichia coli - Yu, M. T. (1970)
By means of RNA-DNA hybridization with DNA from different merodiploids of Escherichia coli, the genes for 16S and 23S ribosomal RNA were found near minute 74 of the genetic map.